Potret Pengawasan Madrasah Aliyah Se-Kota Samarinda: Antara Cita Dan Fakta - M. Said Husin; Etty Nurbayani (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2013)
This research portraits the supervision for the State Islamic Senior High Schools (MAN 1 and MAN 2) Samarinda. It focuses on the competence, the achievement, and the system run by a MAN supervisor-Samarinda Ministry of Religious Affairs (MORA). Generally speaking, the supervisors have undertaken their profession well. Although, their skills and the results in doing so vary one to another, but these imply no significant different. In terms of the competence, some of whom have accomplished a qualified minimum standard. And all of them, supported by various integrated backgrounds, such as academic and teaching experience, have succeeded to do any kinds of supervision matters. This success can be taken into account as one of the challenging parameters of their commitment to do some valuable efforts for MAN teachers’ qualities and the advancement for a MAN system of academic qualities as well. Yet, as far as the system of supervision is concerned, many of these supervisors, in the view of supervisees, are regarded less capable in providing a professional academic supervision services. In reality, the limitation in numbers, regulations and profits are the problems for a supervisor in doing his or her supervisor affairs, but they are not among the prime factors influence his or her professionality.